2016
DOI: 10.1016/j.jgr.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anti-inflammatory activities of Korean Red Ginseng-derived components

Abstract: BackgroundAlthough Korean Red Ginseng (KRG) has been traditionally used for a long time, its anti-inflammatory role and underlying molecular and cellular mechanisms have been poorly understood. In this study, the anti-inflammatory roles of KRG-derived components, namely, water extract (KRG-WE), saponin fraction (KRG-SF), and nonsaponin fraction (KRG-NSF), were investigated.MethodsTo check saponin levels in the test fractions, KRG-WE, KRG-NSF, and KRG-SF were analyzed using high-performance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 34 publications
4
64
0
Order By: Relevance
“…Similar results were reported by a study that demonstrated saponins obtained from Camellia oleifera effectively removed sebum (Chen, Yang, Chang, Ciou, & Huang, 2010). In addition, red ginseng has been reported by various studies to have anti-inflammatory effects in vitro (Baek et al, 2016) and in vivo (Lee & Cho, 2017), and in this study, too, improvement of early stage inflammatory symptoms such as papules was clinically demonstrated. Thus, red ginseng extracts that contain red-ginseng-derived antimicrobial substances are expected to control the symptoms of acne effectively by not only killing P. acnes but also removing sebum and exerting anti-inflammatory effects.…”
Section: Clinical Trialssupporting
confidence: 91%
“…Similar results were reported by a study that demonstrated saponins obtained from Camellia oleifera effectively removed sebum (Chen, Yang, Chang, Ciou, & Huang, 2010). In addition, red ginseng has been reported by various studies to have anti-inflammatory effects in vitro (Baek et al, 2016) and in vivo (Lee & Cho, 2017), and in this study, too, improvement of early stage inflammatory symptoms such as papules was clinically demonstrated. Thus, red ginseng extracts that contain red-ginseng-derived antimicrobial substances are expected to control the symptoms of acne effectively by not only killing P. acnes but also removing sebum and exerting anti-inflammatory effects.…”
Section: Clinical Trialssupporting
confidence: 91%
“…A luciferase construct that contained promoters sensitive to NF-κB was used as reported previously [20]. Fetal bovine serum (FBS), antibiotics (penicillin and streptomycin), phosphate-buffered saline (PBS), DMEM, RPMI 1640, and trypsin were obtained from Gibco (Grand Island, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted using TRI reagent®, and cDNA was synthesized from 1 μg of total RNA using reverse transcriptase, according to the manufacturer's instructions. Quantitative real-time PCR was performed using qPCRBIO SyGreen Mix Lo-ROX dye, according to the manufacturer's instructions as reported previously (Baek et al, 2016). The primer sequences used for PCR are listed in Table 1. 2.9 | Enzyme-linked immunosorbent assay RAW264.7 cells and splenocytes were treated with escalating doses of Mc-eWE (0-400 μg/ml) for 24 and 12 hr, respectively.…”
Section: Cell Viability Assaymentioning
confidence: 99%